2007
DOI: 10.1063/1.2426937
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen content on the structural and electrical characteristics of thin neodymium oxide gate dielectrics

Abstract: Optical, electrical, and structural characteristics of yttrium oxide films deposited on plasma etched silicon substrates J.The structural properties and electrical characteristics of thin Nd 2 O 3 gate oxides were deposited on silicon substrates by reactive rf sputtering. The structural and morphological features of these films were studied, as a function of the growth conditions ͑three various argon-to-oxygen flow ratios: 20/ 5, 15/ 10, and 12.5/ 12.5 and temperature from 600 to 800°C͒, by x-ray diffraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The as-deposited sample for Tm 2 O 3 film has high level of thulium as compared to the annealed sample. This result is due to the formation of silicate film during thermal annealing, which is in agreement with the literature reported [5][6][7]. In contrast, the Tm 2 Ti 2 O 7 film annealed at 700 and 800 8C has the highest thulium of all samples examined, as shown in Fig.…”
Section: Structural Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…The as-deposited sample for Tm 2 O 3 film has high level of thulium as compared to the annealed sample. This result is due to the formation of silicate film during thermal annealing, which is in agreement with the literature reported [5][6][7]. In contrast, the Tm 2 Ti 2 O 7 film annealed at 700 and 800 8C has the highest thulium of all samples examined, as shown in Fig.…”
Section: Structural Propertiessupporting
confidence: 92%
“…The HfO 2 -based dielectric is likely to employ within this process technology, but it is widely believed that HfO 2 -based technology permits the downscaling of equivalent oxide thickness no further than below $0.8 nm [4]. In addition to the HfO 2 -based dielectrics, rare-earth (RE) metal oxide, such as La 2 O 3 , Pr 2 O 3 , Nd 2 O 3 , Gd 2 O 3 , Dy 2 O 3 , and Er 2 O 3 [5][6][7][8][9][10], is being considered as one of the most promising high-k materials due to its superior properties including a high dielectric constant, a large bandgap, and good thermal stability in contact with the Si substrate. However, the moisture absorption is a major problem with RE oxides, leading to a thicker film and a larger flat-band voltage shift [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although Hf-based high-k gate dielectrics have been intensively investigated as candidate for conventional SiO 2 , recently much attention are also given to the rare earth oxides M 2 O 3 (M = La, Pr, Gd and Nd) due to their large band-gaps, high dielectric constants, small lattice mismatch with Si, and good thermodynamic stability in direct contact with Si [194][195][196][197]. Base on the observations from different groups, improved interface stability and reduced leakage currents can be achieved by forming the amorphous silicate as candidates.…”
Section: Rare Earth Oxides and Silicatesmentioning
confidence: 99%
“…Nd 2 O 3 thin film has attracted much attention as a sensing membrane because it has the advantages of high-k value, good lattice matching, and thermodynamical stability with Si substrate [6]. Furthermore, we demonstrated that Nd 2 O 3 dielectrics exhibited excellent electrical properties, including a high electric breakdown field, a low interface trap density, a small hysteresis and frequency dispersion [7].…”
Section: Introductionmentioning
confidence: 95%